A STRATEGIC FRAMEWORK FOR START-UP MEDICAL DEVICE MANUFACTURERS IN SOUTH AFRICA - Maharaj, Ishan; Sunjka, Bernadette Patricia (The South African Journal of Industrial Engineering, 2019)
An exploratory, qualitative study was conducted to establish why local medical device manufacturing firms are not starting up in South Africa. Semi-structured interviews were conducted with local medical device manufacturers to understand the market and the competitive environment in which companies operate, as well as elements of strategy implemented within these companies. The study concluded that local medical device manufacturers were not starting up in South Africa due to the high capital investment required, the prohibitive and unaligned regulatory framework, brand representation and the unwillingness of end users to switch to smaller brands, and cash flow and liquidity problems. Recommendations were made for start-up medical device manufacturers to mitigate any potential problems that might be faced, as well as for future policy development of medical devices. Included in this was the suggestion to realign South African medical device regulations with other successfully implemented regulations across the world.